Ethical Trade and Moral Integrity: The Crisis of Ethics and Morality in Contemporary Indonesian Commerce and Its Relevance to Al-Ghazali, Ibn Khaldun, and Classical Islamic Thought - Hikam Muhtadi Zuhdi; Dewi Fatmasari; Abdul Aziz (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This article examines the crisis of ethical, moral, and virtuous values in contemporary economic and trade practices, which are still prevalent in many regions of Indonesia. This crisis is marked by the neglect of public rights, deceptive and manipulative investment schemes based on speculation, and the commercialization that erodes the spiritual dimensions of economic actors. Phenomena such as the unilateral and coercive use of public spaces and facilities without regard for public access, economic and trading activities that neglect religious obligations, and the proliferation of investment schemes promising instant profits all indicate a significant moral and ethical degradation in economic (muamalah) practices. This study employs a qualitative method with a normative-philosophical approach, examining the thoughts of Al-Ghazali, Ibn Khaldun, and classical Islamic scholars (salaf) concerning ethics, morality, and virtuous conduct in economic activities. The findings reveal that trade in Islam is not merely about ensuring the smooth functioning of economic transactions or pursuing profit by any means necessary. Rather, it serves as a domain for moral and ethical formation, reflecting the ideals of Maqasid al-Shariah, particularly in the preservation of wealth (hifz al-mal), life (hifz al-nafs), and religion (hifz al-din). This article strongly emphasizes the urgency of reconstructing ethical economic and trade practices grounded in moral values and Islamic teachings as a foundation for sustainable economic development and social stability, both globally and particularly within the Indonesian contex.